الٌظام القانوني لعقد الامتياز الفلاحي في الجزائر - بلقاسن ساهـــي (My University, 2022)
راهنت الحكومة الجزائريةعلى القانون رقم 10/03 المؤرخ في 15 أوت 2010 المحدد لشروط وكيفيات استغلال الأراضي الفلاحية التابعة للأملاك الخاصة للدولة كإطار قانوني يحمل في طياته أهداف إقتصادية لتطوير الفلاحةالوطنيةوعصرنتها قصدتحقيق الأمن الغذائي والتقليص من التبعية الغذائية للخارج،وجعل القطاع الفلاحي بديلا استراتيجيا لقطاع المحروقات. وقد عمد المشرع الجزائري من خلال هذا القانون ضبط وتنظيم عقد الامتياز الفلاحي لتحقيق مقاربة الموازنة بين ضمان إستغلال واستثمار الأراضي الفلاحية التابعة للأملاك الخاصة للدولة وبين موجبات حمايتها والمحافظة عليها، وذلك من خلال العديد من الأحكام التي تضمن حق المستثمر الفلاحي لاستغلال تلك الأراضي وتشجعه على الاستثمار الحر فيها عن طريق توضيح نمط استغلالهاوالتعاملبشفافية تامة مع مستغليها والعمل على إيجاد حلول ناجعة لكافة المشاكل في إطار شفاف وواضح لطمأنة الفلاح الحقيقي، كل ذلك من أجل مواكبة عملية عصرنة الفلاحة من جهة، وضمانحماية تلك الأراضي والمحافظة عليهابالحيلولة دون تملكهاأوالمضاربة أوالمتاجرة بها وإعطاء أساس عقلاني ومصداقية قانونية للتنظيم العقاري الجديد وتعزيز الرقابة عليها من جهة أخرى. ويبدو أن المشرع اعتمد نمط الامتياز لاستغلال الأراضي الفلاحية التابعة للأملاك الخاصة للدولة دون أن يضبطه جيدا من الناحية القانونية، ويتضح ذلك جليا من خلال ظهور العديد من الاشكالات القانونية والعملية بعد تطبيقه والتي أثرت سلبا على الانتهاء من تعميم هذا النمط، مما جعل السلطات المعنية تتدخل باستمرار عن طريق التعليمات والمناشير من أجل حلحلة تلك الإشكالات التي لازال بعضها عالقا إلى غاية اليوم. كما يمكن القول أنه لازالت هناك تحديات كبيرة أمام الدولة وأمام المشرع تحتاج إلى قرارات حاسمة وتظافر كل الجهود لتطبيق حق الامتياز بشكليحقق النهوض بالقطاع الفلاحي لتحقيق الأهداف المرجوة، ويسمح بحماية الأراضي الفلاحية التابعة للأملاك الخاصة للدولة والمحافظة عليها كمورد طبيعي وملك جماعي للأمة. ---------------------------------- The Algerian government has relied on Law No. 10/03 of August 15, 2010 setting the conditions and modalities for the exploitation of agricultural land, making part of the private domain of the State. This law constitutes a legal framework that encompasses economic objectives to develop agriculture in Algeria and modernize it in order to ensure food security, reduce food dependence on foreign countries and make the agricultural sector a strategic substitute for the hydrocarbons sector. The Algerian legislator aimed, through this law, to regulate and organize the contract of agricultural concession to concretize a balanced approach between, on the one hand, the guarantee of the exploitation and the investment of the agricultural lands, coming under the private domain of the State and, on the other hand, the requirements for the protection and conservation of these lands, to this end, the law devotes a number of provisions aimed at guaranteeing the right of agricultural investors to exploit these lands, encouraging them to invest them freely by clarifying the type of exploitation, to behave in complete transparency vis-à-vis the farmers and to work to find efficient solutions to all problems in a transparent and clear framework to reassure the effective farmer, all of thatmeasures come with the intention of protecting and conserving these lands by prohibiting their possession or making them the object of speculation or commercialization, by providing a rational and credible legal basis for the new land organization and by consolidating the control applied to these lands. It seems that the legislator has opted for a type of concession of agricultural landbelonging to the private domain of the State, without clearly specifying its legal regime. This is notoriously noticed by the emergence of several legal and practical problems as a result of the application of the said law, which did not allow the finalization of the generalization of this type of investment and led to recurrent interventions of the concerned authorities through circulars and instructions to solve these problems, some of which persist till today. It can also be said that great challenges are facing the State and the legislator and require decisive measures and a synergy of all efforts to apply the agricultural concession in a way that allows the development of the agricultural sector towards reaching the intended aims, protecting agricultural land forming part of the private domain of the State and preserving it as a natural resource and collective property of the nation. Keywords: Concession, The contract of concession, The exploitation,Agricultural land, The private domain of the State.